KOSMOLOGI SEJARAH DALAM FILSAFAT SEJARAH: ALIRAN, TEORI, DAN PERKEMBANGAN - Mohammad Maiwan (LITERASI: Indonesian Journal of Humanities, 2013)
Cosmology of history is part of the philosophy of history that thorougly examines: causes, principles, nature, characters, patterns and goals of history. In the philosophy of history, there are two schools of thought relating to the issue of history movement: dynamic school of thought and the static school of thought. Meanwhile, there are different perspectives on the pattern of history. The first is a perspective arguing that the pattern of historical movement as linear. The second perspective believes that the pattern of historical movement is circular. Third, there is also a perspective arguing that history has a cyclical pattern. Based on this reality, the interpretation to movement pattern and changes of history is not single but multiple in nature. Keywords: history, philosophy, cosmology